Концепция создания виртуальных средств дистанционного образования - Левыкин, В. М.; Куземин, А. Я. (УАДО, 2002)
Education material construction for distance studying is provided on the base of labor market system analysis and existing educational standards.
Keywords: дистанционное образование; виртуальные средства